Motivations and Expectations of Undergraduate Nursing Students Undertaking International Clinical Placements - Gower, Shelley; Duggan, Ravani; Dantas, Jaya; Boldy, Duncan (2016)
BACKGROUND: International clinical placements are common in preregistration nursing programs in Australian universities to enhance awareness of cultural needs and global health issues. Yet, little is known about the motivations and expectations of nursing students who choose to participate. METHOD: Using a qualitative exploratory design, individual semistructured interviews were undertaken with 52 preregistration final-year nursing students from four Western Australian universities 2 weeks prior to departure to the developing countries of Tanzania, Thailand, the Philippines, Cambodia, and India. Data were analyzed using thematic analysis. RESULTS: The interviews revealed that students were motivated by cultural inquisitiveness and a desire to help. They expected to gain cultural learning, to be challenged, to be fulfilled, to experience professional growth, and to feel gratitude. Developing an understanding of culture was a crucial outcome. CONCLUSION: By understanding the impetus and personal motivations of students, educators can guide students toward a more transformative experience whereby a more multicultural perspective on health care can be developed.